2021
DOI: 10.1128/mbio.02824-21
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-β-Catenin Signaling in Human Dendritic Cells Mediates Regulatory T-Cell Responses to Fungi via the PD-L1 Pathway

Abstract: The balance between effector CD4 + T-cell and immunosuppressive regulatory T-cell (Treg) responses determines the outcome of an infectious disease. The signaling pathways that regulate human CD4 + T-effector versus Treg responses to the fungi are not completely understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…It has also emerged as an integral component of host responses to infection but its function in the context of immune responses is not fully understood (6870). Recent studies have shown that this pathway can control host processes related to bacterial infection; however, pathogens have evolved strategies to manipulate Wnt-associated processes in order to enhance infection and survival within the human host (6870). The mitogen-activated protein kinase (MAPK) signalling pathway was the second most enriched pathway by this set of genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also emerged as an integral component of host responses to infection but its function in the context of immune responses is not fully understood (6870). Recent studies have shown that this pathway can control host processes related to bacterial infection; however, pathogens have evolved strategies to manipulate Wnt-associated processes in order to enhance infection and survival within the human host (6870). The mitogen-activated protein kinase (MAPK) signalling pathway was the second most enriched pathway by this set of genes.…”
Section: Resultsmentioning
confidence: 99%
“…This pathway contributes to the cell cycle control, cytoskeleton reorganization during phagocytosis and cell migration, autophagy, apoptosis, and a number of other inflammation-related events (68). It has also emerged as an integral component of host responses to infection but its function in the context of immune responses is not fully understood (68)(69)(70). Recent studies have shown that this pathway can control host processes related to bacterial infection; however, pathogens have evolved strategies to manipulate Wntassociated processes in order to enhance infection and survival within the human host (68)(69)(70).…”
Section: Resultsmentioning
confidence: 99%
“…This pathway contributes to the cell cycle control, cytoskeleton reorganisation during phagocytosis and cell migration, autophagy, apoptosis, and a number of other inflammation-related events [66]. It has also emerged as an integral component of host responses to infection, but its function in the context of immune responses is not fully understood [66][67][68]. Recent studies have shown that this pathway can control host processes related to bacterial infection; however, pathogens have evolved strategies to manipulate Wnt-associated processes in order to enhance infection and survival within the human host [66][67][68].…”
Section: Resultsmentioning
confidence: 99%
“…However, immune exhaustion by signaling through checkpoint molecules could prevent effective clearance of the pathogens leading to exacerbated immune responses (44,45). PD-L1 and PD-1 interaction also supports regulatory T cell responses (46)(47)(48)(49)(50). Of note, PD-L1 expression was significantly higher in a group of severe COVID-19 patients as compared to milder patients and was positively correlated with the WHO and Sequential Organ Failure Assessment (SOFA) clinical scores (22).…”
Section: Discussionmentioning
confidence: 99%